Evaluation of aircraft emission at Tribhuvan international airport and its contribution to air quality in Kathmandu, Nepal - Dikra Prasad Bajgai; Kundan Lal Shrestha (Atmospheric Environment: X, 2023)
The recent rise in the number of aircraft flights and the subsequent increase in emissions has raised concerns worldwide, and this increasing trend is expected to continue. This research provides an overall estimation of the landing and take-off cycle (LTO) emissions from Tribhuvan International Airport (TIA) as well as the associated contribution of these emissions to ambient air quality in Kathmandu valley. The aircraft emissions of nitrogen oxides (NOx), carbon monoxide (CO), hydrocarbon (HC), sulfur dioxide (SO2), volatile organic compounds (VOCs), particulate matter (PM10, and PM2.5), and black carbon (BC) during the LTO are estimated for recent 20 years by using the emission factor method. The corresponding contribution to ambient air quality was simulated using AERMOD and Weather Research and Forecasting (WRF) models. The research reveals that total LTO emissions by aircraft at TIA range from 898 to 2123 tonnes per year (2000–2019). The average LTO emissions of NOx, CO, HC, VOC, SO2, PM10, PM2.5, and BC were around 14512, 8142, 2387, 1737, 1247, 481, 472, and 231 tonnes respectively during the period of 20 years. The highest aircraft emission was shown in taxi/idle mode for the LTO cycle, with major constituents being HC and CO. The LTO emissions and their effect on air quality have continually increased. The highest contribution of the LTO emissions on air quality was found in the pre-monsoon season. The dominant pollutants in TIA were nitrogen oxides and its average 24-h concentration was 158.1 μg/m3, which exceeded the National Ambient Air Quality Standard (NAAQS) limit value. Hence, LTO emission significantly contributed to ambient air quality in Kathmandu city.